Revealing The Academic Terrain: A Bibliometric Analysis of AI Virtual Reality Research Patterns - Nurjanah, Vanisa Siti; Herlina, Yuliani Pratiwi (West Science Interdisciplinary Studies, 2024)
"Revealing the Academic Terrain: A Bibliometric Analysis of AI Virtual Reality Research Patterns," the author explores the complex field of academic works that investigate the relationship between artificial intelligence (AI) and virtual reality (VR). Using bibliometric techniques, we carefully investigate the development, patterns, and influential figures in this ever-changing subject. Our investigation reveals the intricate network of academic publications, clarifying trends in publishing trends, cooperation networks, and topical areas of interest. Our study offers useful insights for scholars, practitioners, and policymakers who want a thorough grasp of the present and potential future orientations of AI virtual reality research by negotiating this scholarly landscape.